Role of OmpA2 surface regions of Porphyromonas gingivalis in host–pathogen interactions with oral epithelial cells. Issue 1 (6th September 2016) - Naylor, Kathryn L.; Widziolek, Magdalena; Hunt, Stuart; Conolly, Mary; Hicks, Matthew; Stafford, Prachi; Potempa, Jan; Murdoch, Craig; Douglas, C. W. Ian; Stafford, Graham P.
Abstract: Outer membrane protein A (OmpA) is a key outer membrane protein found in Gram‐negative bacteria that contributes to several crucial processes in bacterial virulence. In Porphyromonas gingivalis, OmpA is predicted as a heterotrimer of OmpA1 and OmpA2 subunits encoded by adjacent genes. Here we describe the role of OmpA and its individual subunits in the interaction of P. gingivalis with oral cells. Using knockout mutagenesis, we show that OmpA2 plays a significant role in biofilm formation and interaction with human epithelial cells. We used protein structure prediction software to identify extracellular loops of OmpA2, and determined these are involved in interactions with epithelial cells as evidenced by inhibition of adherence and invasion of P. gingivalis by synthetic extracellular loop peptides and the ability of the peptides to mediate interaction of latex beads with human cells. In particular, we observe that OmpA2‐loop 4 plays an important role in the interaction with host cells. These data demonstrate for the first time the important role of P. gingivalis OmpA2 extracellular loops in interaction with epithelial cells, which may help design novel peptide‐based antimicrobial therapies for periodontal disease. Abstract : This paper presents evidence that surface exposed loops of the OmpA2 outer membrane protein of the periodontitis causing pathogen Porphyromonas gingivalis directs interaction with oral epithelial cells and inert surfaces during biofilm formation. These data reveal new insight into two processes key to periodontal pathogen virulence and suggest new avenues for antimicrobial strategies for periodontitis.